Think Pair Share Pedagogy Supports Reading Comprehension In Struggling Elementary Learners: Pedagogi Think Pair Share Mendukung Pemahaman Membaca Siswa Dasar Berkesulitan Belajar - Jamiatul Aini; Ikhlasul Ardi Nugroho (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Reading competence provides the essential foundation for academic achievement and long-term scholastic success in basic education. Specific Background Despite this necessity, upper-elementary learners frequently experience persistent literacy challenges, demonstrating poor phonological awareness and mechanical decoding when approaching simple texts. Knowledge Gap Traditional teacher-centered instruction rarely offers the structured peer interaction necessary to address varied cognitive needs or active engagement in modern classrooms. Aims This study investigates the application of a cooperative pedagogical model to foster the decoding and understanding of two-syllable words among fourth-grade students facing literacy deficits. Results Following a two-cycle action research framework, the participants' mean test scores progressed significantly from an initial 59.50 to 83.33. Furthermore, class mastery criteria grew from 0% in the preliminary phase to a complete 100% by the second cycle, alongside a notable transition from passive to active instructional participation. Novelty This intervention uniquely applies structured social constructivist scaffolding to specifically target basic decoding and vocabulary deficits within an older cohort expected to have already mastered these skills. Implications Integrating structured peer-assisted learning frameworks provides a practical strategy to cultivate inclusive, interactive, and student-centered educational environments while reducing reliance on direct teacher intervention. Highlights The cooperative instructional framework shifted mean test scores from 59.50 to 83.33 across two cycles. Classroom mastery levels progressed from zero to full attainment following the peer-assisted intervention. Participants demonstrated significant behavioral transitions from passive observation to active collaborative engagement. Keywords Cooperative Learning; Peer Assisted Instruction; Literacy Difficulties; Social Constructivism; Action Research